Surveying Artisanal Tuna Fishing Statistic in Hormozgan Province - Gh. Razmjo (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 1994)
The coast of the Hormozgan province has been divided into five strata. From west to east, the five geographical strata are, Lengeh, Qeshm Island, Bandar Abbas, Kolahi and Jask. The statistical procedure used in the study takes into consideration four boat type categories that are distinguished on the basis of carrying capacity, 1 ton boats, 1 to 20 tons, 20 to 50 tons more than 50 tons and four gear types; gillnet, trap, hooks, beach seine, with tunas being caught mainly by gillnetters and in minor proportion with lines. No data are available for the Bandar Abbas and Qeshm Island geographical strata. Longtail tuna is dominate species in the tuna catches of the Hormozgan province, followed by the two species of seerfish (Scomberomorus) and by yellowfin tuna. The three main strata; Lengeh, Kolahi, Jask, for which completes sets of catch data is available call be taken as being representative of the three main fishing zones of the Hormozgan province. A. thazard is caught in all the thre....